PENGARUH TEKANAN PISTON PADA PENGATURAN KATUP SOLENOID PROPORSIONAL DUA ARAH TERHADAP LAJU ALIRAN AIR PADA SISTEM KALIBRASI PISTON PROVER OT-400 - Jalu Ahmad Prakosa (Universitas Gadjah Mada, 2012)
In order to use piston prover OT-400 calibrator more effective is to know the relationship between pressure piston and water flow rate. Water flow rate measurement by using piston pressure variation and setting of proportional directional solenoid valve has been done on piston prover OT-400 calibration sytems. Selection variation of piston pressure condition has been done at four measuring points there are 20 PSI, 42.5 PSI, 62.5 PSI and 80 PSI. Giving of voltage variation for ascending and declining to the solenoid is to set the opening and closing its valve. From the measurement results obtained that the water flow rate is proportional to the piston pressure used. Graph of water flow rate (Q) with unit of liters / minute versus the piston pressure (P) with unit of PSI within the setting ofproportional directional solenoid valve on the piston prover OT-400 calibrator has linear type that is Q = 0.002. P + 0.151 with R2=0,998. While the graph of the average uncertainty value of the measuring point versus pressure piston is not a linear form with the smallest value of 2.31% on the use of piston pressure of 80 PSI